2016
DOI: 10.5194/tc-10-2361-2016
|View full text |Cite
|
Sign up to set email alerts
|

A daily, 1 km resolution data set of downscaled Greenland ice sheet surface mass balance (1958–2015)

Abstract: Abstract. This study presents a data set of daily, 1 km resolution Greenland ice sheet (GrIS) surface mass balance (SMB) covering the period 1958-2015. Applying corrections for elevation, bare ice albedo and accumulation bias, the highresolution product is statistically downscaled from the native daily output of the polar regional climate model RACMO2.3 at 11 km. The data set includes all individual SMB components projected to a down-sampled version of the Greenland Ice Mapping Project (GIMP) digital elevation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
259
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 168 publications
(283 citation statements)
references
References 39 publications
6
259
2
Order By: Relevance
“…yr −1 . A major improvement upon Noël et al (2016) is that no additional precipitation correction is required here as the remaining negative bias in the GrIS interior has been almost eliminated in RACMO2.3p2 (Fig. 11a).…”
Section: Downscaled Smb To 1 Kmmentioning
confidence: 99%
See 2 more Smart Citations
“…yr −1 . A major improvement upon Noël et al (2016) is that no additional precipitation correction is required here as the remaining negative bias in the GrIS interior has been almost eliminated in RACMO2.3p2 (Fig. 11a).…”
Section: Downscaled Smb To 1 Kmmentioning
confidence: 99%
“…To solve these issues at the margins, we apply the downscaling technique described in Noël et al (2016), which includes elevation and ice albedo corrections. As a result, modelled run-off increases by 82 Gt yr −1 (∼ 37 %) to 305 Gt yr −1 for the period 1958-2015, compared to the 11 km product, and the SMB biases and RMSEs in the GrIS ablation zone are reduced by 480 and 460 mm w.e.…”
Section: Downscaled Smb To 1 Kmmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the fields are corrected for the altitude difference induced by the difference of resolution between and by GRISLI (resolution 5 km). This procedure can be followed at a daily time scale (Noël et al, 2016). For our purpose, we choose to average the daily vertical gradients at the annual time scale and to apply the altitude correction every year.…”
Section: Coupling Methods and Experimentsmentioning
confidence: 99%
“…To resolve the finer details that are more useful for prescribed regions or for complex process studies, regional climate models (RCMs) are useful for dynamically down-scaling these climate projections. In Greenland, the RCMs RACMO (e.g., Ettema et al 2009;Noël et al 2016), MAR (e.g., Fettweis et al 2017Fettweis et al , 2013, and PolarMM5 (Burgess et al 2010) as well as HIRHAM5 ) have previously been used for climate research. A comparison of the performance of early versions of these RCMs in Rae et al (2012) showed some differences in performance.…”
Section: Introductionmentioning
confidence: 99%